2002
DOI: 10.1086/338962
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Tully-Fisher Relation of Spiral Galaxies

Abstract: We present the B-band Tully-Fisher relation (TFR) of 60 late-type galaxies with redshifts 0.1 − 1. The galaxies were selected from the FORS Deep Field with a limiting magnitude of R = 23. Spatially resolved rotation curves were derived from spectra obtained with FORS2 at the VLT. High-mass galaxies with v max 150 km/s show little evolution, whereas the least massive systems in our sample are brighter by ∼ 1 − 2 mag compared to their local counterparts. For the entire distant sample, the TFR slope is flatter th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(138 citation statements)
references
References 29 publications
15
119
4
Order By: Relevance
“…Pioneer studies, most of them in the B-band, seem to show evolution, although there was no consensus on whether this evolution was on slope, zero point, or both. Ziegler et al (2002) find a shallower relation at high redshift (z = 1) than what has been measured in local samples. In their study, they claim that less massive galaxies were 1 or 2 mag brighter in the past (at fixed rotational velocity), while the most massive would follow the local relation.…”
Section: Introductioncontrasting
confidence: 67%
“…Pioneer studies, most of them in the B-band, seem to show evolution, although there was no consensus on whether this evolution was on slope, zero point, or both. Ziegler et al (2002) find a shallower relation at high redshift (z = 1) than what has been measured in local samples. In their study, they claim that less massive galaxies were 1 or 2 mag brighter in the past (at fixed rotational velocity), while the most massive would follow the local relation.…”
Section: Introductioncontrasting
confidence: 67%
“…The atomic gas masses cover a range from 1.1 × 10 9 M up to 3.8 × 10 10 M with a median mass of the order of 6.2 × 10 9 M . Considering the upper (Schöniger & Sofue 1997;Sakai et al 2000;Ziegler et al 2002). The H i detected sources from this work are coded with grey-scale.…”
Section: Discussionmentioning
confidence: 99%
“…As the inclinations for the sources in this sample are not defined, we can only assume a range of rotation velocities. By inserting graphs for the TullyFisher relation from literature sources (see e.g., Sakai et al 2000;Ziegler et al 2002) we can estimate where our host galaxies should be found in this graph. Since the majority of the 45 • points as well as the value for the median are located to the left of the literature Tully-Fisher functions our objects should feature lower inclination angles of about 30 • , which is in good agreement with our assumption of a nearly face on inclination for low luminosity AGN.…”
Section: Morphologymentioning
confidence: 99%
“…The circular velocities for the late-type galaxies in Table 1 V c have been estimated using the recent results of Ziegler et al (2002), which measure the B-band TF slope and normalization for mag, focal reducer/low dispersion spec-R ! 23 0.5 !…”
Section: The Lensesmentioning
confidence: 99%
“…estimated from the scatter around the best fit in Figure 3 of Ziegler et al (2002). These errors are propagated in the calculation of the Einstein radius, etc., and account for most of the uncertainty in the final value of the magnification.…”
Section: The Lensesmentioning
confidence: 99%